The story of Amelia Earhart - De Leeuw, Adele 1899-; Beckhoff, Harry (New York Grosset & Dunlap, 1955)
A biography of the woman who was the first female passenger on a transatlantic plane flight and who went on to set many records as a pilot.
Keywords: Earhart, Amelia -- 1897-1937.